Respuesta :
Answer: (x-1)
Step-by-step explanation:
To solve this problem you must apply the proccedure shown below:
1. You have that the terms x²-1 are perfect squares:
x²-1²
2. Therefore, by definition, you have that the difference of squares formula is:
a²-b²=(a+b)(a-b)
3. Therefore, keeping the information above on mind, you have:
x²-1²=(x+1)(x-1)
Then, the missing factor is (x-1)
Answer:
(x-1) is the answer.
Step-by-step explanation:
We have given an incomplete equation.
(x+1)(____) =x²-1
We have to find the missing factor.
Since, we use following formula:
(a+b)(a-b) = a²-b²
By comparing formula with given equation,
In given equation, a = x and b = 1
(x)²-(1)² = (x+1)(x-1)
Hence, the missing factor is (x-1).